Kapita selekta : Strategi dan hubungan internasional - Habib, A. Hasnan; Centre for Strategic and International Studies (Jakarta : Centre for Strategic and International Studies, 1997)
Indonesia foreign relations
Includes bibliographical references
Keywords: Indonesia -- Foreign relations